The Influence of Social Media on Public Awareness of Halal Certification - Abidin, Zaenal; Niskaromah (Zabags International Journal of Engagement, 2025)
This study investigates the influence of social media on public awareness of halal certification among residents of Kampung Laut, Kuala Jambi. As halal certification becomes increasingly important in Indonesia’s growing halal industry, understanding the role of digital platforms in shaping public knowledge and perception is crucial. The research aims to analyze the extent to which exposure to halal-related content on platforms such as Instagram, TikTok, Facebook, and YouTube affects individuals’ awareness and attitudes toward halal certification. A quantitative approach was employed using a structured survey distributed to active social media users within the target population. The findings reveal a positive and statistically significant relationship between the frequency of social media use and the level of halal awareness. Respondents who frequently engage with halal content tend to show higher levels of understanding and trust toward certified products. These results are interpreted through the lenses of the Uses and Gratifications Theory, the Theory of Planned Behavior, and the Diffusion of Innovation Theory, which together provide a multidimensional framework for understanding the behavioral, motivational, and communicative aspects of halal awareness. This study contributes to the academic discourse by extending halal communication research into coastal, digitally underserved communities, and offers practical implications for policymakers, halal authorities, and content creators seeking to strengthen public engagement with halal principles through social media channels.